The political image of Kurds and ideological representation in the Arab novel in Iraq - سعيد عبد الهادي المرهج هديل حسام الدين (College of Education for Women, 2019)
The novels that we have addressed in the research, Including those with the ideological and political ideology, It's carry a negative image for the Kurds without any attempt to understand, empathy and the separation between politics and the people, The novels were deformation of the image, Like tongue of the former authority which speaks their ideas, Such as (Freedom heads bagged, Happy sorrows Tuesdays for Jassim Alrassif, and Under the dogs skies for Salah Salah). The rest of novels (Life is a moment for Salam Ibrahim, The country night for Jassim Halawi, The rib for Hameed Aleqabi). These are novels contained a scene carries a negative image among many other social images, some positive, and can be described as neutral novels. We can say that there is not a real problem between the Kurds and the Arabs, and what exists is artificially by the policy belonging to the authorities and their parties, in order to serve their interests.